A retrospective cohort study on the seizure risks and outcomes of children with acquired brain injury - Li, Vivien W. Y.; Wang, Yuliang; Tso, Winnie W. Y. (Frontiers in Neurology, 2025)
BackgroundThe purpose of this study is to determine the prevalence, risk factors, and characteristics of seizures and epilepsy in children with acquired brain injury (ABI), and compare their outcomes with children with ABI but no seizures.MethodBasic demographic data, clinical features, brain injury severity, seizure and epilepsy characteristics, and functional and neurodevelopmental outcomes of children with ABI with follow-up of at least 2 years were reviewed. Logistic regression was performed to determine the risk factors for seizures.ResultsThe study included 82 children with ABI due to tumors, trauma, hypoxia, stroke, infection, and neuro-inflammatory disorders. There were 43 (52%) boys. The median age at diagnosis was 2.9 years and median follow-up interval was 5 years. A total of 27 (33%) children experienced seizures and 20 (24%) were diagnosed as having epilepsy. Risk factors for seizures included cortical brain injury (p = 0.013) and central nervous system (CNS) infection (p = 0.001). Among those with seizures, seven had acute seizures within 7 days of ABI. The median time of onset of epilepsy after ABI was 2 years, and five children had refractory epilepsy (RE) needing more than two anti-epileptics. The hazard ratio (HR) for epilepsy in those with cortical brain injuries and CNS infections were 4.582 (95% CI [1.83, 11.49], p = 0.001) and 4.796 (95% CI [1.568, 14.67], p = 0.006), respectively. HR for epilepsy onset in those who had post-stroke seizures were 4.467, 95% CI [1.575, 12.67], p =0.005). Most subjects demonstrated significant improvements in Karnofsky Performance Scale (KPS) scores following rehabilitation (p < 0.0001); however, a greater proportion of children with post-ABI seizures required special educational services (p = 0.025).ConclusionCortical brain injuries, CNS infection and post-stroke seizures significantly increase the risk of epilepsy in children with ABI. While functional improvements were observed after rehabilitation, children with post-ABI seizures more often required special educational support. The identification of risk factors for seizures, time to epilepsy onset, and the functional outcomes can guide subsequent management and counseling.